The role of political parties under deliberative democracy in China - Chen, Si; Zhang, Yixin; Ku Samsu, Ku Hasnita; Ismail, Mohd. Mahadee (Human Resource Management Academic Research Society, 2023)
The paper investigates the function of political parties in China's system of deliberative democracy. Deliberative democracy places a strong emphasis on inclusive decision-making procedures and engaged citizens. It offers insight on the contributions, difficulties, and possibilities encountered by political parties in fostering discourse and encouraging public involvement by evaluating their participation in local deliberative forums and legislative debate. The paper aims to shed light on the political parties' role in China's deliberative democracy by closely examining their contributions to the inclusive discussion, public involvement, and democratic decision-making processes. The paper uses secondary data and were analyzed thematically. The results emphasize the value of openness, responsibility, diversity, and internal party democracy. Political parties must develop these facets inside themselves if they are to play a greater role in encouraging good governance and civic engagement. It advances knowledge of political party dynamics and their possibilities within China's developing deliberative democracy framework.